The Popularity Of Aerobics Dance For Women's Society In Sedentary Lifestyle - Latuheru, Ricardo Valentino; Arfanda, Poppy Elisano; Aprilo, Ians (Department of Physical Education, Sport, Health and Recreation, 2022)
Aerobic exercise is one of the most popular types of physical activity today, one of which is aerobic dance. Aerobic dance is a physical activity that combines rhythmic music and body activities. This study aims to analyze the level of popularity of aerobic dance in South Sulawesi. This study was conducted on 287 female respondents with an age range of 17-55 years. Data retrieval in this study was carried out by filling out questionnaires via a google form. This questionnaire was distributed to women who did aerobics in fitness centers. The distribution of the google form is carried out during February 2022. The results of this study found that respondents who chose aerobics dance at 41%, aerobics with using different equipment at 17%, aerobics with elements of martial arts at 15%, aerobics with psychically - regulatory orientation, and water aerobics at 13% each. This study concludes that aerobic dance is the most and most popular choice made by South Sulawesi women’s society.